2011
DOI: 10.1620/tjem.224.127
|View full text |Cite
|
Sign up to set email alerts
|

Short Sleep Duration and Irregular Bedtime Are Associated with Increased Behavioral Problems among Japanese Preschool-Age Children

Abstract: Sleep problems are known to be risk factors for subsequent emotional and behavioral difficulties in childhood and adolescence. To date, there has been no study investigating the relationships between sleep habits and behavioral problems in a large nonclinical sample of preschool age children. The aim of this study was to examine these relationships and factors associated with the sleep habits of preschool age (2 to 5 year old) children. Their mothers (n = 1,746) completed a multiple-choice questionnaire about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 31 publications
(45 reference statements)
3
35
0
1
Order By: Relevance
“…The findings obtained in our study are, however, in line with those of other studies; Komada et al [13] reported that attention and aggressive behavioral problems were not associated with sleep duration, but rather with bedtime irregularity in 4-5-year-old Japanese nursery school children. In Komada's study, parent-reported sleep duration was divided into short and long sleep groups by the median value (9.3 h), and behavioral problems were assessed using the Children's Behavioral Check List (CBCL).…”
Section: Discussionsupporting
confidence: 93%
“…The findings obtained in our study are, however, in line with those of other studies; Komada et al [13] reported that attention and aggressive behavioral problems were not associated with sleep duration, but rather with bedtime irregularity in 4-5-year-old Japanese nursery school children. In Komada's study, parent-reported sleep duration was divided into short and long sleep groups by the median value (9.3 h), and behavioral problems were assessed using the Children's Behavioral Check List (CBCL).…”
Section: Discussionsupporting
confidence: 93%
“…We found that a sleep duration ≥10.01 hours was the most crucial factor in attention performance among preschool children, compared with bedtime, television-viewing time, caregiver education level and children's age. Short sleep duration and irregular bedtime are associated with increased attention problems among Japanese preschool children [1]. Vriend et al [3] and Scharf et al [30] indicated similar findings that manipulating sleep duration alters attention performance in children.…”
Section: Association Demographic Variable Sleep Habit (Bedtime Sleementioning
confidence: 87%
“…Sleep plays a critical role in child neurobehavioral development [1][2][3]. Poor sleep habits, such as delayed bedtimes and insufficient sleep durations, are risk factors for subsequent daytime sleepiness, reduced attention, and aggressive behavior in childhood [1,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations